EFFICIENCY AND LEGAL CERTAINTY IN THE RESOLUTION OF INDUSTRIAL RELATIONS DISPUTES IN BATAM’S INDUSTRIAL AREA - Banar Maejaya; Indra Sakti; Agus Riyanto; Rizki Tri Anugrah Bhakti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Abstract (TNR11) This article examines the effectiveness of alternative dispute resolution mechanisms, particularly mediation and arbitration, in the settlement of industrial relations disputes in Batam’s industrial area, with emphasis on two principal parameters: efficiency and legal certainty. Batam occupies a distinctive place in Indonesia’s economic geography as a free trade zone, an industrial cluster, and a strategic investment hub. This position generates intensive labour relations and, inevitably, a significant volume of industrial disputes. At the same time, the Industrial Relations Court (Pengadilan Hubungan Industrial/PHI) serving the Riau Islands Province is located in Tanjungpinang rather than in Batam. For workers and employers in Batam, this institutional arrangement increases travel costs, procedural burdens, and the time required to obtain formal adjudication. Using a normative juridical method supported by statutory, conceptual, case, and document-based approaches, this study analyses legislation, court decisions, institutional reports, scholarly literature, and verifiable secondary empirical information relating to dispute settlement practice in Batam. The study finds that mediation has become the dominant and relatively effective mechanism because it reduces costs, shortens processing time, and filters a substantial number of disputes before they reach litigation. However, legal certainty remains less than optimal due to persistent weaknesses in the execution stage, the non-binding nature of mediators’ recommendations, the underutilization of arbitration, and the absence of a PHI in Batam. The article therefore argues for stronger mediation institutions, the establishment of a local PHI in Batam, enhanced labour-law literacy, and better harmonisation between central and local policy as essential steps toward a dispute resolution system that is faster, fairer, and more legally certain. Keywords: Alternative Dispute Resolution; Arbitration; Legal Certainty; Mediation; Industrial Relations Disputes